On development of functional brain connectivity in the young brain - Hoff, G.E. Anna-Jasmijn; Van Den Heuvel, Martijn; Benders, Manon J.N.L.; Kersbergen, Karina J.; de Vries, Linda S. (Frontiers in Human Neuroscience, 2013)
Our brain is a complex network of structurally and functionally interconnected regions, shaped to efficiently process and integrate information. The development from a brain equipped with basic functionalities to an efficient network facilitating complex behavior starts during gestation and continues into adulthood. Resting-state functional MRI (rs-fMRI) enables the examination of developmental aspects of functional connectivity and functional brain networks. This review will discuss changes observed in the developing brain on the level of network functional connectivity (FC) from a gestational age of 20 weeks onwards. We discuss findings of resting-state fMRI studies showing that functional network development starts during gestation, creating a foundation for each of the resting-state networks to be established. Visual and sensorimotor areas are reported to develop first, with other networks, at different rates, increasing both in network connectivity and size over time. Reaching childhood, marked fine-tuning and specialization takes place in the regions necessary for higher-order cognitive functions.